Using Problem Based Learning (PBL) to Improve Critical Thinking Skills and Indonesian Language Skills - Tampubolon, Grace; Sianturi, Hanna; Sitotus, Jelita; Simbolon, Yesika; Siregar, Rosdiana; Tansliova, Lili (CV. Rayyan Dwi Bharata, 2024)
The use of problem based learning (PBL) to improve critical thinking skills and Indonesian language skills, to improve students' critical thinking skills, problem based learning (PBL) is the right learning model to use. The purpose of problem-based learning is to find out how problem-based learning can help students in improving their critical thinking and language skills. The subject in this study focuses on how students' Indonesian language skills. Data collection techniques are done by observation and finding references from various research journals. The research method used in this study is quantitative method, quantitative research to try to find out how effective PBL is in improving certain skills, such as critical thinking and Indonesian language skills. PBL model can serve as a useful tool to improve students' critical thinking and Indonesian language skills.